An Investigation on the Correlation of Inter-story Drift and Performance Objectives in Conventional RC Frames - Saeed Rastegarian; Ashkan Sharifi (Ital Publication, 2018)
The main objective of this study is interpreting the probable dependency of structural performance level and its corresponding inter-story drift in conventional RC moment frames. For this purpose, inter-story drift as dependent variable and other structural characteristics such as strength of materials, structural dimensions and internal loads as independent variables have been assumed. Specimens were studied by means of pushover analysis, then independent and dependent variables have been recorded for each member. Correlation of all variables were examined extensively and finally accurate equations have been proposed to predict inter-story drift at performance objectives.